A study of multicast behaviour - Phua, Kia Ming. (2008)
This report describes the design and implementation of Mgat, a real-time web-based multicast graphical analysis tool that allows network managers to observe traffic patterns and easily detect potential problems in their multicast network. Mgat utilizes existing tools to collect and display session and path trace information on Real-time Transport Protocol (RTP) based on streaming audio and video sessions, and presents a global snapshot view of the multicast sessions as seen from its multicast host.